Caging the rainbow : places, politics, and aborigines in a North Australian town - Merlan, Francesca (Book collections on Project MUSE., 1998)
Explores the lives of Aborigines in the small town of Katherine, Australia. The author combines ethnography and theory to study issues surrounding the debate about the authenticity of contemporary cultural activity. The vulnerability of Fourth World peoples to others' representations of them and the ethical problems this poses are recognised.